Semiotika Generasi Sandwich di Film Home Sweet Loan - Rosanti Rosanti; April Laksana; Putri Handayani; Rizqi Fitrianti; Meiby Zulfikar (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The film Home Sweet Loan depicts the reality of the lives of young people who face economic and psychological pressures due to the double burden of family. The character of Kaluna represents the sandwich generation, a generation that must meet the needs of both generations, parents and the nuclear family. This study aims to analyze the meaning of denotation, connotation, and myth in this film, as well as how the representation of the sandwich generation is formed through narrative and visual symbols. The approach used is Roland Barthes' semiotic analysis, which divides meaning into three levels: denotative, connotative, and myth. Data were obtained through observation of the film, visual documentation and dialogue, and interviews with semiotics experts and film practitioners. The results show that the film Home Sweet Loan presents a layered meaning that reflects the dilemma of the sandwich generation, especially young women. The representation of the sandwich generation is formed through symbols and narratives that highlight the conflict between personal interests and responsibilities to the family. This film not only reflects reality but also functions as an ideological medium that shapes society's perspective on the role of the younger generation in the modern family. Through the character of Kaluna, the film depicts the pressures experienced by individuals in this position, including the challenge of maintaining a balance between personal ambition and obligations to the family. Thus, this film conveys a message about the importance of balancing personal interests and social demands within the family.